2016
DOI: 10.1080/10803548.2015.1071926
|View full text |Cite
|
Sign up to set email alerts
|

Protective clothing for pesticide operators: part I – selection of a reference test chemical for penetration testing

Abstract: A systematic approach was taken to develop a database for protective clothing for pesticide operators; results are reported as a two-part series. Part I describes the research studies that led to identification of a pesticide formulation that could serve as a reference test chemical for further testing. Measurement of pesticide penetration was conducted using different types of pesticide formulations. Six fabrics were tested using 10 formulations at different concentrations. Three formulations were subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…It is likely that fabric construction and fabric weight were major factors affecting pesticide penetration through the garments. Our results are in agreement with a study by Shaw and Schiffelbein [19], which found that fabric weight and repellent finish were the significant factors affecting pesticide penetration. Previous studies also stated that other characteristics of fabrics such as thickness, yarn twist factor, cover factor, critical surface tension, and solid volume fraction, were significant parameters [18,21].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is likely that fabric construction and fabric weight were major factors affecting pesticide penetration through the garments. Our results are in agreement with a study by Shaw and Schiffelbein [19], which found that fabric weight and repellent finish were the significant factors affecting pesticide penetration. Previous studies also stated that other characteristics of fabrics such as thickness, yarn twist factor, cover factor, critical surface tension, and solid volume fraction, were significant parameters [18,21].…”
Section: Discussionsupporting
confidence: 93%
“…Most agricultural workers wore work clothing made of woven fabric when working on farms, resulting in the easy penetration of pesticides through to the skin [1,17]. Pesticide penetration through woven fabric depends on type of pesticide, fabric thickness, fabric weight, yarn twist, and fabric composition [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is that fabric C1-R had the most weight when compared with other fabrics. Fabric weight had an effect on penetration level of pesticides through fabrics (Shaw & Schiffelbein, 2016b). Therefore, it can be concluded that fabric C1-R is the one most likely be suitable for conferring protection against all these pesticides during spraying and other associated handling activities.…”
Section: Discussionmentioning
confidence: 96%
“…They also found that a thickness of fabric above 0.8 mm has the highest level of effectiveness in providing protection against pesticides. In addition, a study by Shaw and Schiffelbein (2016b) also stated that fabric weight and repellent finish affected percentage penetration more than test chemicals. Our results therefore suggest that the fabrics made of 100% cotton and have greater weight serve as the first choice for protective clothing when spraying pesticides and related tasks on the farm.…”
Section: Discussionmentioning
confidence: 99%
“…However, PPE such as protective clothing can lose its efficiency of use after pesticide sprays and multiple washes [5]. Some studies demonstrated that the pesticide formulation at different concentrations could affect the protection of the protective clothing [20].…”
Section: Machines and Laborers Used In Cutting Rubber Plantationmentioning
confidence: 99%